Pengaruh Penambahan Ekstrak Buah Pepaya Muda (Carica papaya L) pada Pakan untuk Pertumbuhan dan Kelangsungan Hidup Benih Ikan Nila (Oreochromis nilotius) - Rustiana Widaryati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2018)
This study aims to determine the effect of giving young papaya fruit extracts (Carica papaya L) in feed on growth and survival of Tilapia (Oreochromis nioticus). The study used a completely randomized design (CRD) with 3 (three) treatments. Treatment A feeding with the addition of papaya fruit extract 1 gr/kg, treatment B 1.5 gr/kg, and treatment C 2 gr/kg. The parameters observed were relative weight growth, survival and water quality. The results showed that feeding with the addition of young papaya fruit extracts gave a significant effect on the growth of tilapia seeds where the highest treatment was in treatment C (2 gr/kg) of 100.14% followed by treatment B (1.5 gr/kg) of 86.29% and treatment A (1 gr/kg) of 58.18%. Based on the results of follow-up tests between treatments given showed a significant difference between treatments. This means that the more extracts given are the better for increasing the growth of tilapia. The survival of tilapia seeds were 100% in each treatment. Water quality was in the range that can still be tolerated by Tilapia seeds. Keywords : Tilapia (Oreochromis niloticus), Carica papaya L, feed, growth.